(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines fundamental changes in modern demographic processes, their specific aspects, territorial and geographical changes in the demographic activity of young people, the essence of state youth policy. The influence of the human factor, socio-economic processes on the age and gender composition and qualitative changes in the economic development of countries in the era of globalization is analyzed. The article also highlights the content of the concept of demographic activity of the population and its modern significance in the life of society.